Resistência ao cisalhamento e grau de conversão: efeito de diferentes protocolos de fotoativação na colagem de bráquetes metálicos - Cruz, Itanielly Dantas Silveira (2017)
Objective: To analyze the effect of different photoactivation protocols on shear bond strength (SBS) of metallic brackets bonded to enamel and the degree of conversion (DC) of an orthodontic resin using three photoactivating devices. Methodology: 230 crowns of bovine incisors were randomly distributed in 23 groups (n = 10). After the surface treatment with phosphoric acid (15 seconds) and Primer Transbond XT (3M Unitek), metal brackets were bonded to the enamel with Transbond XT resin (3M Unitek) using 23 photoactivation protocols according to the factors "photoactivator" (FlashMax P4 – RMO, Valo Cordless – Ultradent or Radii-Cal – SDI), "photoactivated faces" (center/vestibular; mesial, distal, cervical and incisal; mesial and distal or cervical and incisal) and "photoactivation time" (2, 3, 4, 6, 20 or 40 seconds). The shear test (100KgF, 1mm/min) was performed after storage of the samples for 4 months (distilled water, 37°C). Using the same photoactivation protocols, 230 resin discs (0,1 mm thick and 5 mm diameter, on average) were made for DC analysis. The SBS (MPa) and DC (%) data were evaluated descriptively and through Student's T-test, one-way ANOVA and the Tukey test. The union failures were classified according to the Adhesive Remnant Index (ARI), analyzed descriptively and through the Kruskal-Wallis test. Results: Of all 23 protocols, only 5 presented clinically accepted SBS values according to the literature. Regarding the factors "photoactivated faces" and "photoactivation time", the Valo Cordless protocols were the only ones that presented statistically similar SBS results (p=0,230 and p=0,093, respectively). Of the comparisons that presented a statistically significant difference (p≤0,05) regarding the factor "time of photoactivation" according to SBS, 66,6% corresponded to the protocols where only the central face of the bracket was photoactivated. When comparing the groups where only two faces were photoactivated, those in which the pair of faces corresponded to the mesial and the distal were the ones that resulted in higher SBS values. Regarding the CG, considering the "photoactivated faces" factor, only the results of the FlashMax P4 groups were statistically different (p≤0,05). The Valo Cordless was the only device in which the factor "time of photoactivation" didn’t affect statistically means the values of the DC (p=0,968). And the majority (66,6%) of the highest DC values when only two faces were photoactivated corresponded to those protocols in which such faces were mesial and distal. Regarding ARI, there was a statistically significant difference between the scores (p=0,000), and the score 2 was the most observed (52,6%). Conclusion: The SBS of the metal brackets bonded to the enamel and the DC of the Transbond XT resin may present statistically significant differences depending on the selected photoactivating device and the bonding protocol used by the orthodontist. And it’s assumed that the adhesive force between the resin and the dental enamel is greater than that between the bracket and the Transbond XT.